Cyclic voltammetry study of a yeast-based microbial fuel cell - Vilas Boas, J. (2022)
Microbial fuel cells (MFCs) using yeasts are known to produce less energy than those using bacteria. However, yeasts offer a plethora of advantages that can be used to MFCs profit. In this work, the electrochemical behavior of Zygosaccharomyces bailii was investigated by cyclic voltammetry, using a synthetic winery wastewater. The voltammograms revealed different oxidation-reduction peaks that could be associated to substrate oxidation/reduction and flavins production. The voltammograms also revealed an oxidation peak at 0.89V vs SCE with a corresponding current of 418A. This peak current dependency with the scan rate indicated that the kinetics was ruled by diffusion and adsorption processes due to an irreversible electron charge transfer. This could be attributed to the yeast or to the electroactive metabolites excreted. The electroactive metabolites can play an important role in mediated electron transfer in yeast-based MFC systems for energy production and for biosensing and electrosynthesis applications.